Structural similarity between β3‐peptides synthesized from β3‐homo‐amino acids and aspartic acid monomers. Issue 4 (July 2014) - Ahmed, Sahar; Sprules, Tara; Kaur, Kamaljit
ABSTRACT Formation of stable secondary structures by oligomers that mimic natural peptides is a key asset for enhanced biological response. Here we show that oligomeric β3‐hexapeptides synthesized from l‐aspartic acid monomers (β3‐peptides 1, 5a, and 6) or homologated β3‐amino acids (β3‐peptide 2), fold into similar stable 14‐helical secondary structures in solution, except that the former form right‐handed 14‐helix and the later form left‐handed 14‐helix. β3‐Peptides from l‐Asp monomers contain an additional amide bond in the side chains that provides opportunities for more hydrogen bonding. However, based on the NMR solution structures, we found that β3‐peptide from l‐Asp monomers (1) and from homologated amino acids (2) form similar structures with no additional side‐chain interactions. These results suggest that the β3‐peptides derived from l‐Asp are promising peptide‐mimetics that can be readily synthesized using l‐Asp monomers as well as the right‐handed 14‐helical conformation of these β3‐peptides (such as 1 and 6) may prove beneficial in the design of mimics for right‐handed α‐helix of α‐peptides. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 359–367, 2014.